Endoscopic ultrasonography‐guided biopsy using a Franseen needle design: Initial assessment. Issue 3 (20th December 2016) - Bang, Ji Young; Hebert‐Magee, Shantel; Hasan, Muhammad K.; Navaneethan, Udayakumar; Hawes, Robert; Varadarajulu, Shyam
Abstract : Background and Aim: Recently, a 22‐gauge (G) needle with a Franseen tip design was developed for endoscopic ultrasonography‐guided fine‐needle biopsy (EUS‐FNB). The present study evaluated the performance of the Franseen biopsy needle in EUS‐guided tissue acquisition. Methods: This is a retrospective study of patients who underwent EUS‐FNB using the Franseen needle. Lesions were sampled using either the Franseen needle only or after failed diagnostic fine‐needle aspiration (FNA). After rapid onsite evaluation (ROSE), two dedicated passes were carried out for histological assessment using the cell block technique. Main outcomes were: (i) rates of diagnostic adequacy for ROSE and histological diagnosis; and (ii) quality of histology as determined by total tissue area and tumor percentage in tissue. Results: Thirty patients underwent EUS‐FNB of pancreatic or other masses over a 3‐month period. Twenty‐four lesions were sampled using the Franseen needle only and six after failed diagnostic FNA. Final diagnosis was pancreatic cancer in 12, gastrointestinal stromal cell tumor in five, other tumors in four and benign disease in nine. Diagnostic adequacy for ROSE was 96.6% and histological diagnosis was established in 96.7% of patients. Median tissue area was 2.9 mm 2 (IQR = 0.68–8.71 mm 2 ) and median tumor percentage in tissue was 73.9% (IQR = 44–97.6). Rates of technical success and adverse events were 96.7 and 3.3%, respectively. Conclusion: Preliminary data suggest that the Franseen needle yields diagnostic material for ROSE and histology in >95% of patients.